TEACHER'S PERSONALITY DEVELOPMENT IN PROFESSIONAL ACTIVITY AND ADAPTATION TO THE SCHOOL ENVIRONMENT (Scientific journal of the Fergana State University, 2025)
This article analyzes the processes of a teacher's personality development in professional activity and adaptation to the school environment. It discusses how personal growth influences a teacher’s professional skills, pedagogical competence, and level of socio-psychological adaptation. Furthermore, the impact of the school environment on a teacher's personality, the role of the pedagogical team in this process, and adaptation factors are examined. The article provides recommendations for supporting teachers' personal and professional development.